Alpha, Beta and Gamma Taxonomy of Biocontrol Agent Diaeretiella rapae (Hymenoptera, Braconidae) - Nemanja Popović; Korana Kocić; Željko Tomanović; Andjeljko Petrović (Insects, 2025)
Diaeretiella rapae (McIntosh, 1855) is a cosmopolitan koinobiont endoparasitoid of aphids, occurring mainly on crucifers and cereals. From description, it has changed several genera and has about 20 synonyms. The specimens for this study were collected between 1989 and 2023 from sites across Europe and the Middle East. For molecular analysis, the barcode mitochondrial gene COI was used, and morphological analysis was conducted with other Aphidius species. Morphologically, D. rapae falls within the determined variability of the same characters of the genus Aphidius. Dieretiella rapae comprised 23 haplotypes with a mean genetic distance between haplotypes of 0.8%. Phylogenetically, D. rapae is nested within Aphidius species with a genetic distance of 2.1% to 11.3%, which is within the range of other Aphidius species. Our results on morphological and molecular level confirm that D. rapae belongs to the genus Aphidius.